THE INFLUENCE OF GROWTH REGULATORS ON SOYBEAN PRODUCTIVITY IN THE CONDITIONS OF THE NORTHERN STEPPE OF UKRAINE - Shepilova, T. P. (Scientific Progress & Innovations, 2019)
Soybean is traditionally referred to as one of widely spread leguminous crops in the world. It is universally used in food, feed industries, and technology. In Ukraine, along with a large amount of soybean acreage, its productivity remains unstable, mainly due to the violation of cultivation technology. The modern direction of increasing soya yields is applying energy-saving technologies by using plant growth regulators, which enables to increase productivity and improve seed quality. The aim of the research was to identify the effectiveness of growth regulators for the treatment of soybean seeds of different groups of ripeness in the northern Steppe of Ukraine. The research task was to determine the effect of growth regulators on field germination of seeds and soya productivity. Field, laboratory and statistical methods were used in the research. The results of the studies showed that using growth regulators increased field germination of the seeds of early-ripening Zolushka variety by 2.1−2.7 %, and of medium-ripening Romashka variety by 2.2−3.3 %. Concerning the studied growth regulators, X-site preparation (25.8 pcs. with Zolushka variety) and (33.2 pcs. with Romashka variety) had more positive effect on the formation of the number of pods per one plant, which was by 15.7 % and 14.9 % more than the control sample respectively. The seed weight per plant was 7.70 g bigger in Romashka variety on the average and on 6.17 g in Zolushka variety. Using growth regulators contributed to a significant increase in seed weight as compared with the control sample in Romashka variety by 0.34−0.61 g (4.6−8.3 %), Zolushka variety after using Vympel and X-site preparations – 0.44 and 0.51 g, respectively. In both varieties, the formation of a larger seed weight was achieved by treating seeds with X-site preparation – 6.35 g and 7.95 g respectively. Yields showed that all growth regulators ensured their significant increase in Romashka variety – 0.23−0.33 t/ha (by 9.2–13.3 %), in Zolushka (Vympel and X-site – 0.16 and 0.27 t/ha), respectively. In variants with seed treatment with the X-site growth regulator, soybean yields were higher and amounted to 2.46t/ha in Zolushka and 2.82 t/ha in Romashka varieties.